Analisis Faktor- Faktor Yang Memotivasi Mahasiswa Dalam Berinvestasi Saham Pada Aplikasi Ajaib (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Metro) - Japlani, Ardiansyah; Dupri, Muhammad Demsi; Anita, Ria (Jurnal Manajemen DIVERSIFIKASI, 2023)
Adequate knowledge of the correct investment methods is crucial to avoid losses wheninvesting in stock market applications, such as Ajaib. The growth of investors in Ajaib'sapplication is considered quite good. However, when compared to other countries, theinvestment awareness among the Indonesian population is still relatively low. The presenceof numerous new companies can be one of the driving factors for increasing the number ofinvestors, especially in stock market investments through Ajaib's application. However, thesheer number of companies alone may not significantly impact the growth of investors if theawareness of investment among students remains low. The purpose of this research is todetermine the combined influence of interest, profit, and self-efficacy on stock marketinvestments through Ajaib's application among students at Muhammadiyah University Metro.This research uses a quantitative approach, and the research method involves the Slovin formula for sample determination. The sample consists of 56 students from the 2018 class inthe Faculty of Economics and Business at Muhammadiyah University Metro. The dataanalysis techniques include validity testing, reliability testing, normality testing, linearitytesting, and homogeneity testing. The analytical model used in this research includes multiplelinear regression analysis, T-test, F-test, and R-squared determination. Based on theresearch results, the T-test indicates that interest significantly influences stock marketinvestments through Ajaib's application among students at Muhammadiyah University Metro.Profit also has a significant influence on stock market investments through Ajaib'sapplication among these students. On the other hand, self-efficacy does not have a significanteffect on stock market investments through Ajaib's application among students atMuhammadiyah University Metro. The F-test results show that interest, profit, and selfefficacy together have a significant influence on stock market investments through Ajaib'sapplication among students at Muhammadiyah University Metro